2021
DOI: 10.1155/2021/6640133
|View full text |Cite
|
Sign up to set email alerts
|

Affordability of Essential Medicines and Associated Factors in Public Health Facilities of Jimma Zone, Southwest Ethiopia

Abstract: Background. Affordability is one of the key dimensions for access to essential medicines, and poor affordability impedes access to treatment in health facilities. The concept of affordability is associated with the issue of impoverishment and catastrophic expenditure. The provision of affordable and appropriate essential medicines is a vital component of a well-functioning health system. Objective. The objective of this study was to assess the perceived affordability of essential medicines and associated facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The easy availability of herbal medicines as over-the-counter medications may have contributed to their high utilization rate, as the participants may not have felt the need to consult a physician before using them. Affordability and accessibility have been a major factor for more herbal medicine consumption in some countries (22) Furthermore, the perception that herbal medicines are safer compared to pharmaceutical medicines may have encouraged their use, as the general population may have felt that they had a lower risk of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The easy availability of herbal medicines as over-the-counter medications may have contributed to their high utilization rate, as the participants may not have felt the need to consult a physician before using them. Affordability and accessibility have been a major factor for more herbal medicine consumption in some countries (22) Furthermore, the perception that herbal medicines are safer compared to pharmaceutical medicines may have encouraged their use, as the general population may have felt that they had a lower risk of adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of unaffordable medicines in Ethiopia was 72.09% and 91.84% in the public and private sectors, respectively [ 5 ]. Another study reported that 63.9% of the prescribed medicines were unaffordable [ 38 ]. The price of medicines in the private sector is higher than the public sector [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Unaffordable prices and non-availability of medicines have become one of the most pressing concerns for patients and healthcare systems in high-, middle- and low-income countries. 2 , 3 Efforts to ensure access to medicines are mainly driven by an ethical imperative: people should not be denied access to life-saving or health-promoting interventions for unfair reasons, including economic or social causes. 4 Within the African context, certain limitations exist concerning their access to basic medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Medicine affordability is the cost of medicines or treatment with medicines about lowest paid government employees income 2 , 14 that would be required to pay to purchase from the private sector a one-month course of medicine at the standard or common dose. 20 The number of days’ income that the lowest-paid government employee would have to fork over to cover treatment is used as a metric for affordability.…”
Section: Introductionmentioning
confidence: 99%